The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1021/acs.est.1c03452
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Impacts of Microcosm Mass Loss on Kinetic Constant Estimation

Abstract: Microcosm experiments to assess microbial reductive dechlorination of chlorinated aliphatic hydrocarbons typically experience 5–50% mass loss due to frequent sampling events and diffusion through septa. A literature review, however, reveals that models fit to such experiments for kinetic constant estimation have generally failed to account for experimental mass loss. To investigate possible resultant bias in best-fit parameters, a series of numerical experiments was conducted in which Monod kinetic models with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Abiotic batch reactor model fitting revealed that a simple first-order diffusive mass loss term, R i s in eq , underestimated the chlorinated ethene mass in reactors over time (see Figure S5). To avoid potential Monod kinetic parameter estimation bias, an improved method for estimating chlorinated ethene mass loss into the rubber stopper was implemented . This approach used time superposition of an analytical solution for planar diffusion of a chemical compound i from an aqueous phase at concentration C i a into a semi-infinite solid rubber phase…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Abiotic batch reactor model fitting revealed that a simple first-order diffusive mass loss term, R i s in eq , underestimated the chlorinated ethene mass in reactors over time (see Figure S5). To avoid potential Monod kinetic parameter estimation bias, an improved method for estimating chlorinated ethene mass loss into the rubber stopper was implemented . This approach used time superposition of an analytical solution for planar diffusion of a chemical compound i from an aqueous phase at concentration C i a into a semi-infinite solid rubber phase…”
Section: Resultsmentioning
confidence: 99%
“…A numerical model, implemented in SciPy, was formulated to simulate MRD in batch reactors using the following mass balance equation: , normald normald t ( V a C i a ) + normald normald t ( V g C i g ) = V normala R i normalb + R i normals where i corresponds to PCE, TCE, cis -DCE, VC, or ethene, t is time [T], V a and V g are the aqueous and gaseous phase volumes [L 3 ], respectively, C i a and C i g are the aqueous and gaseous phase concentrations [M/L 3 ], respectively, R i b is the overall MRD reaction rate [M/L 3 /T], and R i s is the mass transfer rate [M/T] between the reactor aqueous phase and the stopper. Typical of other MRD models, it was assumed that partitioning between aqueous and gaseous phases conformed to Henry’s law and MRD was governed by Monod kinetics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations